Martin Rantan-Farhan Political Communication In The Regional Head Election In Ketapang District, West Kalimantan Province 2020 - Antir, Antir; Elyta, Elyta; Saherimiko, Saherimiko (International Journal of Education, Vocational and Social Science, 2024)
Political communication is a very important aspect in the political battle process to win council seats at both the central and regional levels. This research aims to describe and identify the political communication carried out by the winning regional head candidate pair Martin Rantan, SH, M.Sos, and Deputy Regional Head H. Farhan, SE, M.Si in Ketapang Regency in 2020. This research uses descriptive qualitative research. with analytical methods. Technique for determining informants using a natural setting. The data sources used are primary data sources and secondary data sources. The data collection technique for this research is by conducting interviews, observation, and documentation/library study. The results of the political communication research examined in this research on the Martin Rantan - Farhan pair as winners of the Regional Head election in Ketapang Regency, West Kalimantan Province in 2020 consist of; communicator, communication message, communication media, and audience. Based on interviews conducted by all sources related to political communication, it can be concluded that several parties were assigned as communicators in the case of the winning team, the Martin Rantan – Farhan pair, namely a successful team that was felt to have communicator abilities and performance as well as high credibility. The communication message of the couple Martin Rantan-Farhan is expressed in the form of socialization with the characteristic jargon, namely "Ketapang is progressing towards a prosperous society". The communication media used are very varied, such as using social media in the form of Facebook, Instagram, and Twitter for millennial voters, in addition to using door-to-door brochures/pamphlets, as well as banners and technical guidance. The audience, namely the entire community in Ketapang Regency, felt that there were several weaknesses in the political communication carried out but this did not reduce the enthusiasm of the audience or the public for the Martin Rantan – Farhan pair so that they could win the regional elections in 2020.